ENGLISH IMPERIALISM IN THE OTTOMAN EMPIRE IN THE LATE 19TH – EARLY 20TH CENTURY (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This study explores the political, economic, and cultural impact of British imperialism on the Ottoman Empire during the late nineteenth and early twentieth centuries — a period marking capitalism’s transition to its imperial phase. Using historiographical analysis and documentary evidence, the article examines how Great Britain employed financial instruments, diplomatic alliances, and cultural discourse to extend its influence over the weakening Ottoman state. It reveals that British control operated primarily through indirect economic dependence, exemplified by debt commissions, the acquisition of Suez Canal shares, and the annexation of Cyprus. The research also highlights the interplay between imperial strategies and Orientalist narratives that justified British hegemony under the guise of modernization and reform. The Tanzimat reforms, the Crimean War alliances, and the Treaty of Sèvres are analyzed as turning points illustrating the transformation of Ottoman sovereignty. The findings demonstrate that British imperialism not only reshaped the political geography of the Middle East but also contributed to the ideological foundations of modern Turkey’s emergence from the ruins of the Ottoman order.